(3ebGdI GdEScfOQ GdEaQhOjSi aj GdMS hcja gh Ydi ePgH CQSWhs - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3bGd GdEScfOQ (B: (3Ef CQSWh deG aQZ ef cJGHg GdPi jOYi cJGH GdfaS ef Gdbhd ai UaI GdbhI GdZGRjI , CQOa bhdg HUaI GdMS hcja jchf s
(3BNQgG (B:s
(3JeJ GdebGdI ai GdMSf, hGdMeO ddg cKjQkG ceG gh Cgdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/5) s
Keywords: (3GdadSaI hGdefWbs